Analysis on Cooperative communication in Wireless Body Area Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Body Area Networks (WBANs) can be used to monitor medical, sporting, ortraining-related activities (WBAN). Placed either inside or around a person's body, these sensors areused to collect health data via wireless transmission while they are engaged in a specific activity (IEEEstandard 802.15.6). An effect device is connected to sensors via these nodes. During this paper, we havea tendency to detail a handful of integral diseases and its subordinate diagnostic tests in normal,moderate, critical condition mode, protocols of a WBAN and cooperative communication in WBAN.These will provide the fundamental plan regarding WBAN. Compared with basic or simple networkcommunication, the cooperative communication in WBAN the facility of the signal and quality of thesignal is hyperbolic and it provide secured network between the companions and therefore the simplicityof the exchange of the information. For efficient transmission or reception, a sufficient number ofcooperative nodes is selected based on channel conditions and transmitted distance.Cooperative communication in WBAN is employed for to monitor the patient health condition with theassistance of relays for single or dual patient health monitoring or for multi patient health monitoring in indoor or outdoor and accustomed to improve the system performance and making monitoring efficient. These we can implement by using Lab view, NS, MATLAB to get simulative results